Provenance of obsidian artifacts from the Natural Protected Area Laguna del Diamante (Mendoza, Province Argentina) and upper Maipo valley (Chile) by LA-ICP-MS method - De Francesco, Anna Maria (2017)
By means of inductively Coupled Plasma Mass Spectrometry associated with Laser Ablation (LA-ICP-MS)we analyzed several obsidian artifacts from the Natural Protected Area Laguna del Diamante (Mendoza,Argentina) and upper Maipo valley (Chile). This analytical method, almost non-destructive, is a powerfultool for the determination of trace elements and is very useful in characterizing and determining the provenance of obsidian fragments of archeological interest, although care must be taken to avoid oraccount for heterogeneities within obsidian such as microcrysts.In the macro-region of study, two types of sources can be differentiated on the basis of their primary location: high-altitude sources emplaced in the Andes range (2500 m a.s.l.) including Laguna del Diamante, Laguna del Maule, and Las Cargas sources; and low-altitude (1500 m a.s.l.) extra-Andean sources situated on the eastern plains: Cerro Huenul and El Pece~no. In addition, while the primary location of Arroyo Paramillos source is currently unknown, we consider it as a sub source of Laguna del Diamante, since its wide archaeological distribution has a main core within Laguna del Diamante area and in the upper Maipo River basin. Considering this pattern, the assignation of provenances presented here improves the basis for assessing the use of high Andean environments from both sides of the mountain range. In addition, we will also improve the geochemical discrimination between the two sources Arroyo Paramillos and Las Cargas that based on only previous XRF analysis are chemicallyoverlapping, leading to an incorrect interpretation of their pattern of archaeological distribution. The better characterization of the obsidian sources of the Laguna del Diamante and neighboring regions allows discussions of mobility, exchange, and human use of this lithic resource in the highland of central western Argentina - central Chile.